IMPLEMENTATION OF MOSQUE MANAGEMENT IN IMPROVING PROSPERITY AND INFRASTRUCTURE - Ahsan Fatkhunnajib; Yetty Faridatul Ulfa; Sukari Kusuma Septiarum (Jurnal Scientia, 2023)
Implementation of mosque management is the application of management sciences that provide greater autonomy to institutions in this case mosque management, where all mosque takmirs agree to increase independence, flexibility, participation, openness, cooperation, accountability, and initiative in managing, utilizing, and empowering all mosque takmirs. Implement mosque management includes Plan (planning), Do (doing/organizing), Control (supervising), and Action (implementation/implementation). Abbreviated as P.D.C.A. There are two approaches to realising management: internal and external. The internal approach is to maximize all mosque takmirs who can evaluate themselves in total all stakeholders and the external approacis h in terms of the involvement of worshippers and the community. Supporting actors in implementing mosque management are the high commitment and loyalty of all mosque takmirs supported by adequate infrastructure facilities, while the dominant inhibiting factors are related to costs and lack of understanding related to social media and IT mastery.